Ex-ante impact of on-farm diversification and forward integration on agricultural value chain resilience: A system dynamics approach. (April 2021) - Aboah, Joshua; Wilson, Mark M.J.; Bicknell, Kathryn; Rich, Karl M.
Abstract: Objective: This paper examines the ex-ante impacts of on-farm diversification and forward integration strategies on agricultural value chain resilience, with an empirical focus on Ghana's cocoa value chain. Method: System dynamics modelling was used to explore five scenarios involving variable-input on-farm diversification pursued by cocoa farmers in Ghana and the simultaneous adoption of forward integration strategies by Ghana and Cote d'Ivoire. Results and Conclusions: An adaptive strategy involving the simultaneous pursuit of variable-input on-farm diversification and a cooperative forward integration strategy by both Ghana and Cote d'Ivoire was found to result in the highest level of resilience. Under such an adaptive strategy, in-country processors will be the most impacted when the level of safety stocks are below 25% of the average stock level during the period of losses in raw material production. Significance: The findings suggest that a policy direction that supports on-farm diversification and in-country processing enhances the aggregate resilience of the cocoa value chain, irrespective of the forward integration strategy adopted by Cote d'Ivoire. Highlights: On-farm diversification improves the resilience of the cocoa value chain. A complementarity exists between diversification and forward integration strategy. Ghana's cocoa value chain is resilient when in-country processing levels increase.